Proposal for a model of Integrated Management System of Documents and Information for organizations - del Prado Martínez, Miguel Ángel; Esteban Navarro, Miguel Ángel (Revista General de Información y Documentación, 2016)
The aim is to elaborate a model of integrated management system of documents and information for organizations with an approach focused on processes. To achieve this target the study analyses the scientific literature and a case study of three corporations. The conceptual and operational principles of the information system are exposed. The objectives, components and subsystems structure commons to an integrated system are indicated. The six stages of the design, planning and assessment method are described. It concludes that this proposal can serves as a basis for some guidelines to any organization by a standardizing institution or accepted as prescriber by the profession
Keywords: Document information systems; Integrated information systems; Records management; Document management; Information management in the Organizations; Design and planning; Assessment.